Race, colonial history and national identity: Resident Evil 5 as a Japanese game - Martin, Paul (SAGE, 2016)
Resident Evil 5 is a zombie game made by Capcom featuring a White American protagonist and set in Africa. This paper argues that approaching this as a Japanese game reveals aspects of a Japanese racial and colonial social imaginary that are missed if this context of production is ignored. In terms of race, the game presents hybrid racial subjectivities that can be related to Japanese perspectives of Blackness and Whiteness where these terms are two poles of difference and identity through which an essentialised Japanese identity is constructed in what Iwabuchi calls “strategic hybridism” (Iwabuchi, 2002). In terms of colonialism, the game echoes structures of Japanese colonialism through which Japanese colonialism is obliquely memorialised and a “normal” Japanese global subjectivity can be performed.